IOT MONITORING WATER NEEDS IN RICE FIELDS - Nanang Prihatin; Hari Toha Hidayat; Mursyidah; Hafhis Gustiawan (PT. Radja Intercontinental Publishing, 2024)
Water management is a very important role in the success of increasing rice production in fields. This study took a case study on irrigated rice fields. In an effort to improve the quality and efficiency of water management in rice fields, a good monitoring system is also needed. Generally, monitoring has been done manually so far, the interaction between farmers and irrigation officers is still using the telephone, which costs a lot of money. With the IoT (Internet of Things) technology, it can be applied to a monitoring system for managing water needs in rice fields using mobile-based AHP, which is a system that provides notifications in the form of information on water levels and the best humidity values for rice plants in rice fields in real-time and is able to deliver reports via internet transmission media. This study aims to obtain the value of report delivery speed through monitoring applications and to be able to detect water levels and soil moisture in paddy fields using the Analytical Hierarchy Process (AHP) method and sensor accuracy so that the results are as expected. The research data has been obtained by looking at the suitability of soil moisture information in the application with the ETP302 measuring instrument with an accuracy value of 86.12% and the water level in applications with an actual water level of 66.35%. In testing the speed of sending reports an average value of 1.67 s. In the best soil moisture detection test using the AHP method, the suitability value is up to 91.7% and the water level reaches 93.4%. The sensor can also be turned off or on through the monitoring application.